Improving the Spectral Response of Black Dye by Cosensitization with a Simple Indoline Based Dye in Dye-Sensitized Solar Cell - Md. Akhtaruzzaman; Ashraful Islam; Mohammad Rezaul Karim; A. K. Mahmud Hasan; Liyuan Han (Journal of Chemistry)
Indoline dye D-1 was successfully applied as a cosensitizer for improving the spectral response of black dye in dye-sensitized solar cells (DSCs). It was observed that D-1 effectively increases the short-circuit photocurrent by offsetting the competitive light absorption by I/I3- electrolyte in the wavelength region 350–500 nm when adsorbed on the TiO2 nanocrystaline films in a mix dye system. The DSCs containing the D-1 and black dye achieved a power conversion efficiency of 9.80% with higher short-circuit photocurrent of 19.54 mA/cm2 compared to the system of black dye without cosensitization under standard AM 1.5 sunlight.